Strategic business tax planning - Karayan, John E (John Wiley & Sons, 2007)
Strategic Business Tax Planning, Second Edition is the definitive handbook on business tax planning, skipping the unnecessary and minute taxation details and focusing instead on the big picture in taxes. Organized around business processes, this reader-friendly guide shows you how to optimally put tax management principles to work in your business.